SCREENING FOR INTESTINAL PARASITES IN ADULTS FROM THREE DIFFERENT REGIONS OF COLOMBIA - Hernán Carvajal-Restrepo (Asociación Colombiana de Infectología, 2019)
Intestinal parasitosis (IP) is a public health problem in developing countries affecting one fourth of the global population. IP are common studied in children, neglecting the adults that are also at high risk and source of transmission. A screening study was performed with a convenience sample in three Colombian regions: Guachené (Cauca), Quibdó (Chocó), and Urabá (Antioquia). Feces samples from 284 volunteers (older than 18 years old) were tested by microscopy to identify parasite ova and cysts. The IP frequency was 14.5%, and 52.1% were males. 63.2% of the parasitized patients exhibited diarrhea, and/or abdominal pain with significant association. 39.5% had single parasitic infection and 60.5% had multiple parasites: Blastocystis hominis (63.9%), Entamoeba hystolitica/dispar (39.4%), Endolimax nana (33.3%), Ascaris lumbricoides (22.2%), Giardia lamblia (19.4%), Entamoeba coli (13.9%), Trichuris trichiura (11.1%), hookworm species (11.1%), Strongyloides stercolaris (5.6%), and Iodamoeba butschlii (2.8%). A multivariate approach was used to determine predictor factors for IP: male gender, rainwater as drinking source, and feces disposal different to toilet, latrine or septic tank were positively associated with infection. This study evidences that adult population, not only children from vulnerable areas of Colombia, must have to include as a risk for intestinal parasitism.